2012
DOI: 10.1103/physrevb.86.235423
|View full text |Cite
|
Sign up to set email alerts
|

Efros-Shklovskii variable-range hopping in reduced graphene oxide sheets of varying carbonsp2fraction

Abstract: We investigate the low temperature electron transport properties of chemically reduced graphene oxide (RGO) sheets with different carbon sp 2 fractions of 55 to 80 %. We show that in the low bias (Ohmic) regime, the temperature (T) dependent resistance (R) of all the devices follow Efros-Shklovskii variable range hopping (with T ES decreasing from 30976 to 4225 K and electron localization length increasing from 0.46 to 3.21 nm with increasing sp 2 fraction. From our data, we predict that for the temperature ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
127
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(148 citation statements)
references
References 61 publications
18
127
0
3
Order By: Relevance
“…Also, our transmission electron microscopic images 22 suggest that the ribbons have a nonuniform structure. The VRH-type electron transport mechanism has also been reported in several other graphene-derived materials such as reduced graphene oxide 23 and patterned GNR. From the slope of the VRH-fitting, the characteristic temperature (T o ) is estimated at ∼784 K. Previous studies 23 have reported the characteristic temperature as high as 1800 K in highly reduced graphene oxide materials.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Also, our transmission electron microscopic images 22 suggest that the ribbons have a nonuniform structure. The VRH-type electron transport mechanism has also been reported in several other graphene-derived materials such as reduced graphene oxide 23 and patterned GNR. From the slope of the VRH-fitting, the characteristic temperature (T o ) is estimated at ∼784 K. Previous studies 23 have reported the characteristic temperature as high as 1800 K in highly reduced graphene oxide materials.…”
Section: Resultsmentioning
confidence: 93%
“…The VRH-type electron transport mechanism has also been reported in several other graphene-derived materials such as reduced graphene oxide 23 and patterned GNR. From the slope of the VRH-fitting, the characteristic temperature (T o ) is estimated at ∼784 K. Previous studies 23 have reported the characteristic temperature as high as 1800 K in highly reduced graphene oxide materials. From T o , the localization length ξ , an indication of edge disorder, is estimated by,…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Such sp 2 fraction tuning can also lead to a variation of work function and bandgap of RGO. [18][19][20][21][22][23][24] However, how the variation of carbon sp 2 fraction of RGO will affect the performance of RGO-contacted OFETs remains unexplored.…”
mentioning
confidence: 99%
“…21 The carbon sp 2 fraction was calculated as 61%, 66%, and 80% for 10, 30, and 60 min of reduction time of RGO sheets, respectively. The carbon sp 2 fraction was obtained by taking the ratio of the integrated peak areas corresponding to the C-C peak, to the total area under the C 1s spectrum from the X-ray photoelectron spectroscopy (XPS) ( Figure S1 in the supplementary material).…”
mentioning
confidence: 99%